The suitability of cryptocurrency in the structure of Islamic banking and finance - Ibrahim Mohammed Lawal (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This paper tends to examine cryptocurrency and its permissibility in the structure of Islamic banking finance. It identifies the major types of cryptocurrencies and also revealed its benefits. Despite these benefits and relating it to Islamic finance it was viewed from two angle; cryptocurrency and money in Islam and also cryptocurrency and the principles of Islamic finance. The study revealed it is compatible to structure of Islamic banking and finance when compared side by side to the features of fiat money which is currently in use. More so, the study clears some of the key issues like its legal tender, issuer unknown, money laundering & illicit purpose etc usually raised against cryptocurrency. The study concluded that cryptocurrency as an economic innovation has secured a pass mark to fit into the structure of Islamic banking and finance. The study further recommends that there is need to create standards guiding its operations, further ensure full disclosure on its transactions etc.